RBSPICE measurement of ion loss during the 2015 March storm: Adiabatic response to the geomagnetic field change. Issue 10 (11th October 2016) - Soto‐Chavez, A. R.; Lanzerotti, L. J.; Gerrard, A.; Kim, H.; Bortnik, J.; Manweiler, J. W.
Abstract: A strongly energy‐dependent ring current ion loss was measured by the Radiation Belt Storm Probes Ion Composition Experiment (RBSPICE) instrument on the Van Allen Probes A spacecraft in the local evening sector during the 17 March 2015 geomagnetic storm. The ion loss is found to be energy dependent where only ions with energies measured above ∼ 150 keV have a significant drop in intensity. At these energies the ion dynamics are principally controlled by variations of the geomagnetic field which, during magnetic storms, exhibits large‐scale variations on time scales from minutes to hours. Here we show that starting from ∼19:10 UTC on 17 March the geomagnetic field increased from 220 to 260 nT on a time scale of about an hour as captured by RBSPICE‐A close to spacecraft apogee, L = 6.1 and magnetic local time (MLT) = 21.85 h (GSM coordinates X =− 4.89, Y = 3.00, and Z =− 0.73). We demonstrate the relationship between this large geomagnetic field increase and the dropouts of the ≳ 150 keV ring current ions. Key Points: Ring current ion loss due to conservation of third adiabatic invariant Energy‐dependent ion loss strongly correlated with the geomagnetic field change Results and model neither consistent with magnetopause shadowing nor with encountering with the magnetospheric lobe